Voices in forensics: exploring student perceptions of oral presentations and podcasts as assessment tools in forensic science education - Daniel Preece (Journal of Learning Development in Higher Education)
Innovative assessment methods are increasingly being explored to enhance student engagement and learning outcomes. This study examines the effectiveness of podcast assessments as an alternative to traditional written and oral assessments in higher education for forensic science. A mixed-methods approach was used to analyse student perceptions through thematic and Likert-scale feedback on a podcast assessment. Results (n=13) showed that students generally found podcast assessments highly engaging and preferred them over traditional written and oral assessments. Qualitative feedback highlighted deeper engagement, creative expression and a more conversational and flexible format. However, challenges included technical skills, structuring content and the lack of immediate audience feedback. While the majority supported integrating more podcast assessments into future coursework, a minority preferred traditional presentations for their public-speaking benefits. These findings suggest that podcast assessments provide an engaging and student-centred alternative to conventional formats, aligning with contemporary shifts in higher education pedagogy. To maximise their effectiveness, educators should offer structural and technical support while considering hybrid or flexible assessment models. Future research should explore the long-term impact of podcast assessments on learning outcomes across various disciplines.